Historical Life Courses and Family Reconstitutions. The Scientific Impact of the Antwerp COR*-Database - Paul Puschmann; Hideko Matsuo; Koen Matthijs (Historical Life Course Studies)
The Antwerp COR*-database is a longitudinal micro-level database, which covers all entries from individuals whose last names started with the letters COR (and individuals who shared at some moment in time a household with a COR*-person) from the population registers and the vital registration of births, marriages and deaths for the 19th- and early-20th-century Antwerp district in Flanders, the northern Dutch-speaking part of Belgium. As such the database allows the reconstruction of historical life courses and families, and the analysis of key demographic characteristics and developments regarding marriage, fertility, migration, social mobility, health, mortality and longevity, as well as their interplay within and across households, families and generations. After a short description of the source material and the construction of the database, a review of the literature based on the database is presented in order to provide the reader with an encompassing overview of the research that has been carried out with this database and the knowledge and insights it has generated since its first release in 2010. The article ends with a discussion of potential pathways for future research, including new topics, and future extension of the database through citizen science projects.